Fabrication of new single cell chip to monitor intracellular and extracellular redox state based on spectroelectrochemical method. (February 2015) - El-Said, Waleed Ahmed; Kim, Tae-Hyung; Chung, Yong-Ho; Choi, Jeong-Woo
Abstract: Probing the local environment of target cells has been considered a challenging task due to the complexity of living cells. Here, we developed new single cell-based chip to investigate the intracellular and extracellular redox state of PC12 cells using spectroelectrochemical tool that combined surface-enhanced Raman scattering (SERS) and linear sweep voltammetry (LSV) techniques. PC12 cells immobilized on gold nanodots/ITO surface were subjected to LSV and their intracellular biochemical changes were successfully monitored by SERS simultaneously. Moreover, paired gold microelectrodes with micrometer-sized gap containing hexagonal array of gold nanodots were fabricated to detect electrochemical activity and changes in the redox environment of single PC12 cell based on SERS–LSV tool. This showed very effective detecting method. The used technology included the utilization of gold nanodots array inside micro-gap to enhance the Raman signals and the electrochemical activity of single cell. This could be used as an effective research tool to analyze cellular processes.